Sleep pattern and academic performance of undergraduate medical students at universiti Kebangsaan Malaysia - Harlina Halizah Siraj, Abdus Salam, Raihanah Roslan, Nurul Ashiqin Hasan, Tan Hiang Jin, Muhammad Nazim Othman (Journal of Applied Pharmaceutical Science, 2014)
Sleep is an active, repetitive and reversible state of perceptual disengagement from the environment including unresponsiveness to it. Adequate sleep is extremely important for healthiness. But sleep loss is a remarkable problem in modern society. The objective of this study was to investigate the sleep pattern and its association with students’ academic performance. It was a cross sectional study conducted among 4th year UKM undergraduate medical students of session 2011-2012. Inclusive of all 234 registered 4th year students was selected for this study. A standard questionnaire that contained questions on demography, sleep habits, academic performance and ideal sleep was used to collect data. Out of 234 students, 186 were responded giving a response rate of 79.5% where 73% were female and 69% resided in-campus. Including weekdays and weekends averagely, 56.2% respondents slept for 6-8 hours, 29.1% for 8 hours. An average of 53.35% respondents had in-frequent day-nap, 34.9% frequent and 11.75% had no day-nap at all. Respondents who slept >6 hours were observed to have significantly higher academic performance. It is concluded that, people need to understand the role of sleep and have to take adequate sleep of 6-8 hours per day for health and wellbeing.
Keywords: Sleep pattern, academic performance, medical students.